Museums, Museology, and the Memory of the Elderly: An analysis of Chapter I of the Museology course conclusion work entitled: Thinking about a Museum for the Elderly: Community Implementation Process of the Museum of the Elderly of Brazil – MAIB (Cadernos de Sociomuseologia, 2026)
AbstractThis article focuses on the twilight of life in Brazil, exploring the social reality of the elderly and the fundamental role of memory as a guiding thread through this journey. The central objective is to analyze how museology, in its social vocation, can create spaces for the appreciation and safeguarding of the memories of the elderly population, especially in a context where time accelerates population aging and challenges public policies. The methodology is based on a bibliographic review of concepts related to aging, policies for the elderly, and the social function of museums, taking inspiration from Chapter I of the Museology Course Completion Work that dealt with the implementation of the Museum of the Association of the Elderly in Brazil, in the city of Goiânia, Brazil. The article will examine the biological, psychological, and social aspects of aging, the course of elderly rights in Brazilian legislation, and the resonance of individual and collective memory in people's voices elderly people who make up the institutions. The analysis seeks to uncover the need for spaces that promote dignity and celebrate the wisdom of the elderly, highlighting the potential of museums as guardians of these memories, as well as confirming how spaces intended for the care of the elderly contribute to a better quality of life for those who helped build the world we belong to in all contexts: family, social, political, and economic.Keywords: Aging. Elderly, Memory. Social Museology. Public Policies